Pengaruh Pembiayaan terhadap Peningkatan Pendapatan UMKM pada PT. BTPN Syariah KC. Tanjung Balai - Putri Mildani Sari Sibarani; Syahrul Amsari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research is aimed at customers of banks in particular UMKM perpetrators need sufficient funding to conduct their business which in the end improve their opinion. The influence of financing on the revenue of UMKM category customers on BTPN Shariah KC. Tanjung Balai. BTPN Shariah contributes to the Indonesian economy by creating jobs and reducing poverty. However, the limited capital available to UMKM hampers its development, and this is where Sharia financing can play an important role, so explore how Sharia funding can provide opportunities for UMKM with limited capital to develop its business and contribute to the economic growth of UMKM in Tanjung Balai. With primary data collected through questionnaires, quantitative methods are used in this research. BTPN Shariah KC. Tanjung Balai was asked to answer the questionnaire. A simple linear regression method is used to analyze data using the SPSS 23 program. The results of the research show that the financing variable affects the customer income variable of 69%, as demonstrated by the t-value of 8,048 less than 2,051 with a significance of 0,000. The remaining portion is affected by additional variables that are not included in the research model.